DNA Synthesis Is Activated in Mosquitoes and Human Monocytes During the Induction of Innate Immune Memory - Cime-Castillo, Jorge; Arts, Rob J. W.; Vargas-Ponce de León, Valeria; Moreno-Torres, Ramon; Hernández-Martínez, Salvador; Recio-Totoro, Benito; Claudio-Piedras, Fabiola; Netea, Mihai G.; Lanz-Mendoza, Humberto (Frontiers in Immunology, 2018)
Endoreplication is a cell cycle program in which cells replicate their genomes without undergoing mitosis and cytokinesis. For the normal development of many organisms (from fungi to humans) and the formation of their organs, endoreplication is indispensable. The aim of the present study was to explore whether endoreplication and DNA synthesis are relevant processes during the induction of trained innate immunity in human monocytes and in the Anopheles albimanus mosquito cell line. During the induction of trained immunity in both models, endoreplication markers were overexpressed and we observed an increase in DNA synthesis with an augmented copy number of genes essential for trained immunity. Blocking DNA synthesis prevented trained immunity from being established. Overall, these findings suggest that DNA synthesis and endoreplication are important mechanisms involved in inducing innate immune memory. They have probably been conserved throughout evolution from invertebrates to humans.